PPO.16 Understanding the impact of socioeconomic risk factors on late and moderate preterm birth: A population-based cohort study. (9th June 2014) - Smith, LK; Draper, ES; Field, DJ; Johnson, S; Manktelow, B; Marlow, N; Petrou, S; Seaton, SE; Boyle, EM
Abstract : Introduction: Very preterm birth rates (<32 weeks) have been shown to rise with increasing socioeconomic deprivation but less is known about the impact of socioeconomic deprivation on birth at late and moderate preterm gestations (LMPT; 32–36 weeks). Methods: A geographical population-based birth cohort study of 938 LMPT and 939 term-born (≥37 weeks) singleton babies. Socio-demographic, economic, lifestyle and stress factors were collected in a maternal interview after birth. Maternal education level was explored as a risk factor for late and moderate preterm birth, using multivariable Binomial regression analyses. Further models assessed whether demographic, lifestyle and economic factors explained any of this variation. Results: The odds of delivering a LMPT infant increased with decreasing levels of education (OR 1.60 (1.23 to 2.09) for degree level education compared to no qualifications P = 0.002). This changed little after adjusting for maternal age and ethnicity. Three key economic and lifestyle risk factors explained this variation with education levels: access to a car (OR 1.30 (1.03 to 1.66); smoking during pregnancy (OR 1.28 (1.01 to 1.63) and low levels of fruit and vegetable consumption (OR 1.26 (0.99 to 1.62)) Conclusions: Mothers with low levels of education were at greatest risk of delivering LMPT. Lifestyle behaviours (smoking during pregnancy and poor diet) and access to a car which may limit access to health care services appeared to explain this differential. These findings highlight that socioeconomic risk factors continue to impact on prematurity up until 36 weeks gestation.